Developing Monopoly Game to Teach Speaking Skill at X Grade of MA Sirojut Tholibin: English - Muhammad Nur Shoufil Huda; Istina Atul Makrifah; Widiarini (Prodi Tadris Bahasa Inggris, 2023)
Learning media is significantly required for English learners to reinforce the subject that they studied and to facilitate learning, especially in learning to speak. The mastery of speaking skill became the main goal, so learning speaking needs learning media. This research aims to develop a Monopoly game to teach speaking skills at the senior high school level. To reach that goal, R&D with ADDIE’s model was used the data of the research was used observation, interview, and questionnaire. After the Monopoly game was developed it was validated by media and material validator. The result of material validation obtained 90,6% which means that strongly valid, the result of media validation obtained 82,5% which means that strongly valid, and the result of the student’s satisfaction questionnaire obtained 82,6% which means that strongly valid on the trial process. Based on the material validation, media validation, and students satisfaction questionnaire it can be concluded that developed speaking skills by using the Monopoly game which can be an appropriate media to teach speaking skills in English learning.